Complementary and alternative medicine in urologic oncology - Otto, T; Suhr, J; Rübben, H (Urologe. Ausgabe A, 2003)
The great majority of phytotherapeutic, homeopathic and anthroposophical medicines are subject to the regulations in their respective field of application, implying a simple licensing process. In contrast with conventional medications in the area of oncology, some unconventional agents are given in observation studies without the prior testing of quality, side effects and efficacy that is normal in oncology. Unconventional therapeutics cannot be considered equivalent to placebo preparations. Since they may have an immunomodulatory action, one cannot exclude possible long-term adverse effects, including progression of tumors. To date there is no clear indication for routine use of unconventional therapeutic agents in urological oncology. A scientific evaluation according to the criteria of evidence-based medicine is required. This article presents proven results of treatment with unconventional medicines in urooncology against the background of the respective spectrum of methods.